Identifying Areas of Support in Research and Development for the Manufacturing Sector - Liberty Nolasco (Philippine Institute for Development Studies (PIDS), 1999)
With the onset of globalization, nations are compelled to increase more the level of their competitiveness in the international market. The success of Asian tiger economies such as Japan, Taiwan, Singapore and South Korea has been attributed to their heavy investment in research and development. The Philippines, however, is still in a crucial state of development, but the government can help accelerate through the creation of appropriate, workable and enforceable research and development plans and guidelines. The study deals on the manufacturing sector, focusing on its problems and performance. It also analyzes the extent of the effect of government policies to the sector's participation to and promotion of research and development activities. \
Keywords: 330; research and development sector; manufacturing sector